Basic list of veterinary medical serials, third edition: using a decision matrix to update the core list of veterinary journals - Ugaz, Ana G (Medical Library Association, 2010)
OBJECTIVE: This paper presents the methods and results of a study designed to produce the third edition of the “Basic List of Veterinary Medical Serials,” which was established by the Veterinary Medical Libraries Section in 1976 and last updated in 1986. METHODS: A set of 238 titles were evaluated using a decision matrix in order to systematically assign points for both objective and subjective criteria and determine an overall score for each journal. Criteria included: coverage in four major indexes, scholarly impact rank as tracked in two sources, identification as a recommended journal in preparing for specialty board examinations, and a veterinary librarian survey rating. RESULTS: Of the 238 titles considered, a minimum scoring threshold determined the 123 (52%) journals that constituted the final list. The 36 subject categories represented on the list include general and specialty disciplines in veterinary medicine. A ranked list of journals and a list by subject category were produced. CONCLUSION: Serials appearing on the third edition of the “Basic List of Veterinary Medical Serials” met expanded objective measures of quality and impact as well as subjective perceptions of value by both librarians and veterinary practitioners.